Decimal reduction times of Bacillus spores in fermented shrimp paste (Bagoong alamang) - Reyes, Narish Lacaba
ABSTRACT The study established the D-value of Philippine fermented shrimp paste or bagoong alamang at 80°C and at 85°C. Physico-chemical properties and proximate composition of the sample were also determined and correlated to the resulting D-value. Results revealed that the values for the pH at 6.68 ± 0.03, crude fat at 1.13 ± 0.06, and ash content at 20.06 ± 0.08 were higher than those obtained by other researchers. Meanwhile, water activity (Aw), Total Volatile Nitrogen (TVN), moisture content, protein content revealed values lower than the minimum requirement at 0.696 ± 0.01, 13.91 ± 0.72, 65.13 ± 0.76, and 12.39 ± 0.63, respectively. The salt concentration (20.12 ± 0.74%) was within the range required for a product with high-salt concentration. These results were shown to affect the heat resistance of the test strain. The D80°C and D85°C computed were 1.04 ± 0.03 and 0.96 ± 0.01, correspondingly. These D-values provided efficient annihilation of most Bacillus spores in bagoong. These results may be utilized in establishing the thermal process suitable for bagoong alamang against the test strains, B. sphaericus and B. pumilus.